Quality Management System in Higher Education: A Main Pillar Towards Quality Higher Education - Vonny Tiara Narundana; Yusuf Sulfarano Barusman; Defrizal Defrizal; Budhi Waskito; Habiburahhman Habiburahhman (Penerbit Goodwood, 2026)
Purpose: This study reviews Quality Management Systems (QMS) in higher education, examining key concepts, implementation models, impacts, and challenges. It highlights leadership, accreditation, technology, and quality culture as critical success factors and shows how globalization and digital transformation shape accountability, innovation, and continuous improvement. Methodology/Approach: A qualitative descriptive approach was used through a literature review of 11 Scopus-indexed journals, identified via Publish or Perish with keywords “quality management system in higher education.” The thematic synthesis identified and interpreted the core themes. Results/Findings: The findings show that models such as ISO 9001, TQM, and EFQM are widely adopted and aligned with continuous improvement cycles such as PPEPP. An effective QMS enhances the quality of learning, reputation, and employability. Success depends on leadership commitment, stakeholder engagement and contextual adaptability. Bridging theory and practice is essential for sustainable improvements. Conclusions: Quality management systems in higher education face challenges from diverse stakeholder demands, weak implementation, and limited alignment with ISO 21001:2018. Policies without strong leadership and continuous evaluation are inadequate. TQM offers a comprehensive, evidence-based framework that strengthens the QMS and supports digital integration, engagement, sustainability, and global competitiveness. Limitations: This study is limited to a literature review of 11 selected articles without primary data collection, which may be subject to search bias and researcher interpretation. Contributions: This study consolidates diverse QMS models into a strategic reference for university leaders and identifies research gaps, particularly in integrating advanced technologies such as AI and blockchain.